PENGARUH SENAM JANTUNG SEHAT TERHADAP SIKLUS HAID DAN DISMENOREA PADA PENGUNJUNG DI LAPANGAN BLANG PADANG BANDA ACEH TAHUN 2020 - Edi Cahyady; Dewi Astini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Menstruation is a process in which the lining of the uterus collapses every month in women. Menstrual disorders can include menstrual rhythm disorders, abnormalities in the quantity and duration of menstruation, amenorrhea and dysmenorrhea. Healthy heart gymnastics is a sport that is prepared by always prioritizing the ability of the heart, large muscle movements and joint flexibility, and strive to enter oxygen as much as possible. The design of this study is a cross-sectional study (Cross Sectional Study) that looks at whether there is an effect of healthy heart exercises on the menstrual cycle and dysmenorrhoea in women. From the results of data analysis, H0 is accepted and H1 is rejected. This matterThere is no the effect of heart exercise or physical activity on the menstrual cycle and dysmenorrhoea. Based on the results of my research, there is no significant relationship between heart gymnastics with a ring scale, moderate, or severe on the menstrual cycle. There is no significant relationship between heart gymnastics with mild, moderate, or severe scale on menstrual pain.Keywords: Heart gymnastics, Menstrual cycles, Menstrual pain